The role of the dynamic terrestrial exosphere in the storm-time ring current decay - Gonzalo Cucho-Padin; Gonzalo Cucho-Padin; Cristian P. Ferradas; Cristian P. Ferradas; Mei-Ching Fok; Lara Waldrop; Jochen Zoennchen; Suk-Bin Kang; Suk-Bin Kang (Frontiers in Astronomy and Space Sciences)
The charge exchange interaction between exospheric hydrogen (H) atoms and energetic ions in the terrestrial ring current is a crucial mechanism for dissipating global magnetospheric energy, especially during the recovery phase of geomagnetic storms. Historically, ring current modeling has considered H density distributions temporally static and spherically symmetric owing to the lack of event-specific exospheric models. However, observations of the far-ultraviolet (FUV) emission from exospheric H atoms acquired by NASA’s TWINS Lyman-Alpha Detectors (LADs) unveiled not only spatial asymmetries but also significant temporal variability of this neutral population, particularly during storm time. In this work, we investigate the influence of realistic exospheric H density distributions on the ring current decay during the strong storm on 1 June 2013. To do so, we first estimate time-dependent, three-dimensional (3-D) H density distributions using FUV radiance data acquired by TWINS/LADs with a robust tomographic approach. Then, we use these neutral distributions as inputs for the Comprehensive Inner Magnetosphere-Ionosphere (CIMI) model and simulate the ion ring current behavior as a response to the exospheric dynamics. We compared the resulting ion fluxes with those produced when a static and spherically symmetric H model (Rairden's model) is used. We found that the TWINS-based global hydrogen density beyond 3 RE geocentric distances is, on average, ∼35% larger than that of Rairden’s model during quiet time and increases up to ∼50% during the geomagnetic storm. Consequently, the ring current ion flux during the recovery phase decays faster when the TWINS-based model is used. Our comparison study shows that using a realistic H-density model produces ∼60% lower ion fluxes (H+ and O+ with energy range 0.1–60 keV) than those yielded by Rairden’s model, especially during the recovery phase and at L-shells <4 RE. Also, when the TWINS-based model is used, the total ring current energy during the recovery phase is ∼30% lower than the energy calculated with the static exospheric model.